Ternary positive electrode material, preparation method thereof and electrochemical device

Through the sintering of nickel-cobalt manganese precursor and lithium source and the spray coating technology of amorphous nanocobalt phosphate in liquid phase synthesis, the cobalt phosphate coating layer is formed, solving the electrochemical performance and stability of high-nickel ternary positive electrode materials , achieving more efficient electrochemical performance and large-scale production.

CN119143199AInactive Publication Date: 2024-12-17NANTONG RESHINE NEW MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411617877.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In lithium-ion battery applications, high-nickel ternary cathode materials have problems such as surface residual lithium compounds reducing electrochemical performance and structural instability, resulting in capacity attenuation, which hinders its large-scale application.

Method used

The nickel-cobalt-manganese precursor and lithium source are sintered in primary sintering to form the inner core, and then the amorphous nano-cobalt phosphate coating solution is synthesized through liquid phase for spray coating to form a cobalt phosphate coating layer, and the coating layer is fixed by secondary sintering. , forming a ternary positive electrode material.

Benefits of technology

It improves the structural stability and electrochemical properties of the ternary positive electrode material, reduces the interface impedance, simplifies the process flow, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143199A_ABST
    Figure CN119143199A_ABST
Patent Text Reader

Abstract

The invention discloses a ternary positive electrode material, a preparation method thereof and an electrochemical device, and the preparation method of the ternary positive electrode material comprises the following steps: mixing a nickel-cobalt-manganese precursor and a lithium source, and carrying out primary sintering to obtain an inner core of the ternary positive electrode material; the method comprises the following steps: mixing a phosphoric acid solution, a soluble cobalt salt solution and an alkali solution, and synthesizing a coating solution containing amorphous nano cobalt phosphate through a liquid phase; spraying the coating solution to coat the inner core to obtain a ternary positive electrode material base material; and carrying out secondary sintering on the ternary positive electrode material base material to form a cobalt phosphate coating layer on the surface of the inner core, thereby obtaining the ternary positive electrode material. The amorphous nanometer cobalt phosphate is synthesized through a liquid phase reaction, a uniform cobalt phosphate coating layer is formed on the surface of the inner core of the ternary positive electrode material, and the electrochemical performance and the structural stability of the ternary positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new energy materials, and in particular to a ternary positive electrode material and a preparation method thereof, and an electrochemical device. Background Art

[0002] Lithium-ion batteries have become the main power source for portable electronic devices and electric vehicles due to their high energy density and long cycle life. However, traditional cathode materials such as LiFePO4, LiMn2O4 and LiCoO2 cannot meet the growing market demand due to their insufficient theoretical capacity. High-nickel materials, as alternatives to LiCoO2, have higher theoretical specific capacity and lower cost, and have become a hot topic in current research.

[0003] However, there are some problems in the application of high-nickel ternary cathode materials in lithium-ion batteries. First, the residual lithium compounds on the surface of high-nickel ternary cathode materials will reduce the electrochemical performance of high-nickel ternary cathode materials. Second, the continuous reaction between high-nickel ternary cathode materials and electrolytes during charging and discharging leads to structural instability of high-nickel ternary cathode materials, increases interface resistance, and causes capacity attenuation. These problems seriously hinder the large-scale application of high-nickel ternary cathode materials. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a ternary positive electrode material.

[0005] In addition, the embodiments of the present application also provide a ternary positive electrode material prepared by the aforementioned preparation method and an electrochemical device using the ternary positive electrode material.

[0006] The present invention provides a method for preparing a ternary positive electrode material, which comprises the following steps: Mixing a nickel-cobalt-manganese precursor and a lithium source and sintering them once to obtain the core of the ternary positive electrode material; A phosphoric acid solution, a soluble cobalt salt solution and an alkali solution are mixed, and a coating solution containing amorphous nano-cobalt phosphate is synthesized through a liquid phase; Spray coating the inner core with the coating solution to obtain a ternary positive electrode material substrate; and The ternary positive electrode material substrate is subjected to secondary sintering to form a cobalt phosphate coating layer on the surface of the inner core, thereby obtaining the ternary positive electrode material.

[0007] In some possible embodiments, the soluble cobalt salt in the soluble cobalt salt solution includes at least one of cobalt nitrate and cobalt acetate.

[0008] In some possible embodiments, in the phosphoric acid solution, the mass ratio of phosphoric acid to water is 1:(1-2); In the soluble cobalt salt solution, the mass ratio of the soluble cobalt salt to water is 1:(1-5); The molar ratio of phosphoric acid in the phosphoric acid solution to cobalt in the soluble cobalt salt is (0.6-1):1.

[0009] In some possible embodiments, the alkali solution is a lithium salt solution, and the lithium salt includes at least one of lithium hydroxide and lithium carbonate.

[0010] In some possible embodiments, in the lithium salt solution, the mass ratio of the lithium salt to water is 1:(1-5); The molar ratio of lithium in the lithium salt solution to cobalt in the soluble cobalt salt solution is (1.5-2):1.

[0011] In some possible embodiments, the step of spraying the coating solution to coat the core further includes: The coating solution and the core are heated at a temperature of 100° C. to 120° C.

[0012] In some possible embodiments, the temperature of the secondary sintering is 500° C. to 700° C., and the time of the secondary sintering is 10 h to 12 h.

[0013] In some possible embodiments, the chemical formula of the nickel-cobalt-manganese precursor may be Ni x Co y Mn 1-x-y (OH)2, where 0.8≤x<1, 0 <y<0.2。

[0014] The present application also provides a ternary positive electrode material, which is prepared by the above-mentioned method for preparing the ternary positive electrode material. The ternary positive electrode material includes an inner core containing a ternary positive electrode active substance and a cobalt phosphate coating layer located on the surface of the inner core.

[0015] In addition, an embodiment of the present application further provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode active substance, and the positive electrode active substance is the aforementioned ternary positive electrode material.

[0016] Compared with the prior art, the preparation method of the ternary cathode material provided in the embodiment of the present application is first synthesized by liquid phase reaction of a soluble cobalt source and phosphoric acid under alkaline conditions to form amorphous nano cobalt phosphate. Since amorphous nano cobalt phosphate lacks a long-range ordered crystal structure, it is easier to form a continuous and uniform coating layer during the coating process of the core. In addition, amorphous cobalt phosphate can provide a lower interface impedance, improve the conduction efficiency of electrons and ions, and thus improve the overall electrochemical performance of the ternary cathode material. Secondly, the wet coating process of spray coating is adopted, and the coating layer obtained is more uniform and dense than that of dry coating. At the same time, compared with traditional wet coating, the spray coating process of the present application is simpler and easy to scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A process flow chart of the method for preparing the ternary positive electrode material provided in an embodiment of the present application.

[0018] Figure 2 This is a schematic diagram of the structure of the electrochemical device provided in an embodiment of the present application.

[0019] Figure 3 This is a scanning electron microscope image of the cobalt phosphate synthesized in Example 1 of the present application.

[0020] Figure 4 This is the X-ray diffraction pattern of the cobalt phosphate synthesized in Example 1 of the present application. DETAILED DESCRIPTION

[0021] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0022] Ternary cathode materials have advantages such as good energy density, cycle stability and safety, but they are prone to structural changes and capacity decay during long-term use. In order to overcome the above problems, surface modification or coating of ternary cathode materials is currently common.

[0023] However, the inventors of the present application have found through research that existing coating materials usually adopt traditional metal oxides such as Al2O3, MnO2, MgO, ZnO, TiO2 or V2O5, etc., which have poor electron and ion conductivity, hindering the charge transfer and ion diffusion of ternary cathode materials. As a coating material, phosphate has a strong covalent interaction between metal ions and phosphate groups, has good thermal stability, and can significantly improve the stability of ternary cathode materials during the cycling process; at the same time, phosphate coating can also effectively improve the ion migration ability and electron transfer ability.

[0024] For this reason, please refer to Figure 1 As shown, the embodiment of the present application provides a preparation method of a ternary cathode material, which specifically includes the following steps: Step S1, mixing a nickel-cobalt-manganese precursor and a lithium source and performing a first sintering to obtain the core of the ternary cathode material.

[0025] Specifically, a nickel-cobalt-manganese precursor and a lithium source are mixed in a certain proportion and subjected to a first sintering to obtain the core of the ternary cathode material.

[0026] In some embodiments, the chemical formula of the nickel-cobalt-manganese precursor can be Ni x Co y Mn 1-x-y (OH)2, 0.8 ≤ x < 1, 0 < y < 0.2. Exemplarily, it can be Ni 0.88 Co 0.08 Mn 0.04 (OH)2 or LiNi 0.8 Co 0.1 Mn 0.1 O2, etc. It can be understood that the nickel-cobalt-manganese precursor includes but is not limited to the above range, and its electrochemical performance can be optimized by adjusting the element composition to meet the requirements of different battery applications.

[0027] In some embodiments, the ratio of the number of moles of lithium in the lithium source to the total number of moles of transition metals in the nickel-cobalt-manganese precursor can be (1 to 1.08):1, and further can be (1 to 1.02):1.

[0028] In some embodiments, the lithium source can include at least one of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium acetate, etc.

[0029] In some embodiments, the mixing time can be 15 min to 30 min, which is beneficial to the充分 mixing of the nickel-cobalt-manganese precursor and the lithium source.

[0030] In some embodiments, the mixing method may include mixing, stirring or grinding with a high-speed mixer, etc., which can effectively mix the nickel-cobalt-manganese precursor and the lithium source. It is understood that the mixing method includes but is not limited to the above method, and any method that can achieve mixing of the nickel-cobalt-manganese precursor and the lithium source is possible.

[0031] In some embodiments, the primary sintering process may include: first heating to 500°C~550°C and keeping for 3h~5h to form the preliminary structure of the inner core; then heating to 550°C~750°C and sintering for 12h~15h to promote the crystal growth of the inner core. By controlling the temperature and time of the primary sintering, the crystal structure of the inner core of the ternary cathode material is optimized, which is conducive to improving the rate performance and cycle performance of the ternary cathode material.

[0032] The primary sintering atmosphere may be an oxygen-containing atmosphere, which is beneficial to promoting the oxidation reaction of the nickel-cobalt-manganese precursor and improving the electrochemical performance and stability of the core. The primary sintering atmosphere may further be an oxygen-containing atmosphere with an oxygen concentration of 90% or more, and the oxygen concentration of the oxygen-containing atmosphere may be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, etc.

[0033] Step S2, the phosphoric acid solution, the soluble cobalt salt solution and the alkali solution are mixed, and a coating solution containing amorphous nano-cobalt phosphate is synthesized through liquid phase.

[0034] In this step, amorphous nano cobalt phosphate is prepared by a liquid phase synthesis method to obtain a coating solution containing the cobalt phosphate. Since amorphous nano cobalt phosphate lacks a long-range ordered crystal structure and has a nanometer-scale fine particle size, it is easier to form a continuous and uniform coating layer in the subsequent coating process of the core. In addition, amorphous cobalt phosphate can provide lower interface impedance, improve the conduction efficiency of electrons and ions, and thus improve the overall electrochemical performance of the ternary cathode material.

[0035] Specifically, a phosphoric acid solution and a soluble cobalt salt solution are mixed to obtain an acidic mixed solution, which is then mixed with an alkali solution, and the alkali solution provides an alkaline condition to react to generate cobalt phosphate. Among them, the use of phosphoric acid solution, soluble cobalt salt solution and alkali solution for liquid phase reaction is conducive to obtaining fine and uniform nano-scale cobalt phosphate, which can improve the fluidity of the coating solution on the one hand, which is conducive to the subsequent spray coating, and on the other hand, it is conducive to improving the coating effect and obtaining a uniform and dense coating layer; at the same time, the alkaline condition is conducive to the full reaction to generate cobalt phosphate and reduce the occurrence of side reactions.

[0036] In addition, the mixing method can be dropwise addition, and further can be stepwise addition, which is conducive to the full reaction and reduces the particle agglomeration and large particle precipitation of the product. For example, a phosphoric acid solution is first added dropwise to a soluble cobalt salt solution to obtain a mixed solution, and then an alkali solution is added dropwise to the mixed solution to react to obtain a coating solution.

[0037] In some embodiments, the phosphoric acid solution can be obtained by dissolving phosphoric acid in water, wherein the mass ratio of phosphoric acid to water can be 1: (1-2). Using water as a solvent can reduce impurities, which are easy to remove later and are beneficial to improving the purity of the coating solution. Limiting the mass ratio of phosphoric acid to water to 1: (1-2) is beneficial to optimizing the reaction conditions and facilitating the liquid phase synthesis.

[0038] In some embodiments, the soluble cobalt salt may include at least one of cobalt nitrate and cobalt acetate, etc. The soluble cobalt salt may be illustratively cobalt nitrate, and the nitrogen element in the cobalt nitrate can be released in the form of nitrogen oxide gas during the subsequent sintering process, thereby reducing the risk of impurity introduction.

[0039] In some embodiments, the soluble cobalt salt solution can be obtained by dissolving the soluble cobalt salt in water, wherein the mass ratio of the soluble cobalt salt to water can be 1: (1-5). Using water as a solvent can reduce impurities, facilitate subsequent removal, and help improve the purity of the coating solution. Limiting the mass ratio of the soluble cobalt salt to water to 1: (1-5) can optimize the solution concentration and further improve the uniformity and efficiency of the liquid phase synthesis reaction. The mass ratio of the soluble cobalt salt to water can further be 1: (2-4), and can be 1: 1, 1: 2, 1: 3, 1: 4 or 1: 5, etc.

[0040] In some embodiments, in the mixed solution, the molar ratio of phosphoric acid to cobalt in the soluble cobalt salt can be (0.6-1):1, which is conducive to the formation of amorphous nano-cobalt phosphate. The molar ratio of phosphoric acid to cobalt in the soluble cobalt salt can further be (0.6-0.8):1, illustratively, it can be 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, etc.

[0041] In some embodiments, the alkaline solution can be a lithium salt solution, which can not only provide an alkaline environment, but also replenish lithium for the ternary positive electrode material, thereby enhancing the ionic conductivity of the ternary positive electrode material. During the liquid phase reaction, lithium ions react with nitrates to form lithium nitrate, and during the subsequent sintering reaction, the lithium in the lithium nitrate enters the positive electrode material, thereby achieving the purpose of properly replenishing lithium for the ternary positive electrode material.

[0042] In some embodiments, the lithium salt may include at least one of lithium hydroxide and lithium carbonate, and may further be lithium hydroxide. Lithium hydroxide has high reaction activity and can be carried out at lower temperature conditions or at room temperature while maintaining good reaction efficiency.

[0043] In some embodiments, the lithium salt solution can be obtained by dissolving the lithium salt in water, wherein the mass ratio of the lithium salt to the water can be 1: (1-5). Using water as a solvent can reduce impurities, which is beneficial to improving the purity of the coating solution. Limiting the mass ratio of the lithium salt to the water to 1: (1-5) is beneficial to the full dissolution of the lithium salt, further improving the uniformity and efficiency of the liquid phase synthesis reaction. The mass ratio of the lithium salt to the water can further be 1: (2-4), and can be exemplarily 1: 1, 1: 2, 1: 3, 1: 4 or 1: 5, etc.

[0044] In some embodiments, the molar ratio of lithium in the lithium salt solution to cobalt in the soluble cobalt salt solution can be (1.5-2):1, and a reasonable ratio is conducive to the reaction. The molar ratio of lithium in the lithium salt solution to cobalt in the soluble cobalt salt solution can further be (1.7-1.9):1. Reducing the proportion of lithium within a certain range can retain unreacted soluble cobalt salts and nitric acid in the coating solution, which is conducive to the subsequent coating process. The residual soluble cobalt salts and nitric acid react with the lithium remaining on the surface of the inner core, thereby reducing the residual alkali content on the surface of the ternary positive electrode material. The molar ratio of the two can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc.

[0045] When the soluble cobalt salt is cobalt nitrate and the lithium salt is lithium hydroxide, the reaction equation for the liquid phase synthesis of the coating solution containing cobalt phosphate in this step can be exemplarily: Step S3, spraying the coating solution to coat the inner core to obtain a ternary positive electrode material substrate.

[0046] Specifically, the core obtained in step S1 is first dispersed, and then the coating solution is sprayed on the core in the form of a spray to coat the core to obtain a ternary positive electrode material substrate. Compared with dry coating, the spray coating has a more uniform and dense coating effect, and compared with traditional wet coating, the spray coating is simpler and more efficient.

[0047] In some embodiments, during the spray coating process, the residual soluble cobalt salt and phosphoric acid that have not reacted completely in the coating solution can further react with the residual alkali (such as lithium hydroxide) on the surface of the inner core to form cobalt phosphate, thereby effectively reducing the residual alkaline substances on the surface of the ternary positive electrode material.

[0048] In some embodiments, during the spray coating process, the coating solution and the kernel may be mixed to achieve the effect of spraying and mixing at the same time, which is conducive to further uniformly coating the coating solution on the surface of the kernel. Mixing may include mixing or stirring with a high-speed mixer, etc. It is understood that the mixing method includes but is not limited to the above method, and any method that can achieve mixing of the coating solution and the kernel is acceptable.

[0049] In some embodiments, during the spray coating process, the coating solution and the core may be heated to accelerate the evaporation of water on the surface of the core and reduce the generation of adverse side reactions. The heating temperature may be 100°C to 120°C.

[0050] In some embodiments, the mass ratio of the coating solution to the core can be (0.03-0.1):1, which helps to improve the coating effect and optimize the thickness and performance of the outer coating of the ternary cathode material. The mass ratio of the coating solution to the core can further be (0.05-0.07):1, and can be 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1 or 0.1:1, etc.

[0051] Step S4, secondary sintering the ternary positive electrode material substrate to form a cobalt phosphate coating layer on the surface of the inner core, thereby obtaining a ternary positive electrode material.

[0052] Specifically, the second mixture is placed under certain sintering conditions for sintering to obtain a ternary positive electrode material uniformly coated with cobalt phosphate. Among them, cobalt phosphate is used as a coating layer. Due to the strong covalent interaction between the core transition metal ions and the phosphate groups, the cycle stability of the ternary positive electrode material can be improved; in addition, the amorphous cobalt phosphate can also effectively improve the ion migration ability and electron transfer ability of the ternary positive electrode material. At the same time, since the cobalt phosphate is an amorphous nano cobalt phosphate, the amorphous nano cobalt phosphate lacks a long-range ordered crystal structure, and a continuous and uniform coating layer is formed during the coating process, which effectively improves the coating effect and is conducive to improving the structural stability of the ternary positive electrode material.

[0053] In some embodiments, the atmosphere of the secondary sintering can be an oxygen atmosphere, which is beneficial for the metal ions in the ternary positive electrode material to remain in an oxidized state, reduce the alkali content on the surface of the material, and thereby enhance the electrochemical properties of the ternary positive electrode material.

[0054] In some embodiments, the secondary sintering temperature may be 500°C to 700°C. A higher sintering temperature is conducive to forming a dense coating layer and promoting a tighter bond between the coating layer and the core. The sintering temperature may further be 600°C to 700°C, and may be 500°C, 550°C, 600°C, 650°C or 700°C, etc.

[0055] In some embodiments, the secondary sintering time may be 10 h to 12 h, which is conducive to sufficient sintering. The secondary sintering time may be 10 h, 11 h or 12 h, etc.

[0056] Compared with the prior art, the preparation method of the ternary positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. Amorphous nano-cobalt phosphate is synthesized by liquid phase reaction of soluble cobalt source and phosphoric acid under alkaline conditions, and a continuous and uniform cobalt phosphate coating layer is formed on the surface of the core by spray coating process, thereby improving the structural stability and electrochemical performance of the ternary cathode material. In addition, since the coating layer contains cobalt element, it can effectively improve the ionic and electronic conductivity of the surface of the ternary cathode material, thereby reducing the internal resistance and further improving the electrochemical performance of the ternary cathode material.

[0057] 2. During the formation of the cobalt phosphate coating layer, the unreacted soluble cobalt salt and phosphoric acid can further react with the residual alkali (such as lithium hydroxide) on the surface of the ternary positive electrode material to reduce the residual alkali on the surface of the ternary positive electrode material.

[0058] 3. The spray coating process can efficiently form a uniform and dense coating layer compared to dry coating and traditional wet coating.

[0059] 4. The preparation method is simple and efficient, which is conducive to the large-scale production of ternary positive electrode materials and has excellent commercial prospects.

[0060] The embodiment of the present application provides a ternary positive electrode material, which is prepared by the preparation method of the ternary positive electrode material described above. The ternary positive electrode material includes an inner core containing a ternary positive electrode active material and a cobalt phosphate coating layer located on the surface of the inner core. Since the cobalt phosphate coating layer is amorphous nano cobalt phosphate, the coating layer has a continuous and uniform morphology and has a low interface impedance, which improves the conduction efficiency of electrons and ions on the surface of the positive electrode material, thereby improving the overall electrochemical performance and structural stability of the ternary positive electrode material.

[0061] See also Figure 2 As shown, the embodiment of the present application also provides an electrochemical device (such as a battery), the electrochemical device 100 includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the positive electrode sheet 10 includes a positive electrode active material, and the positive electrode active material is the ternary positive electrode material as described above. The electrochemical device 100 prepared using the ternary positive electrode material has the advantages of high cycle performance and high stability.

[0062] The above-mentioned ternary positive electrode material and its preparation method and electrochemical device are further described below through specific examples.

[0063] Example 1 Step 1: Ni-Co-Mn precursor Ni 0.88 Co 0.08 Mn 0.04 (OH)2 and micro powder lithium hydroxide are mixed, wherein the molar ratio of Li to the transition metal in the nickel cobalt manganese precursor is 1.04:1, and a sintering is carried out in an atmosphere with an oxygen concentration of more than 93%. The first sintering includes first keeping the temperature at 500°C for 5 hours, then heating to 800°C for 15 hours, and then dispersing after cooling to obtain the core of the ternary positive electrode material.

[0064] Step 2: Weigh 490g of cobalt nitrate hexahydrate and completely dissolve it in water, wherein the mass ratio of cobalt nitrate to water is 1:2, to obtain a cobalt nitrate solution; dilute 13g of phosphoric acid in 13g of water to obtain a phosphoric acid solution; drip all of the phosphoric acid solution into the cobalt nitrate solution to obtain a mixed solution. Weigh 12g of lithium hydroxide and dissolve it in 20g of water to obtain a lithium salt solution; slowly drip the lithium salt solution into the mixed solution, and perform a liquid phase synthesis reaction to obtain a coating solution containing amorphous cobalt phosphate.

[0065] Step 3, weigh 10 kg of the above-mentioned core, disperse it in a high-speed mixer for 5 minutes, place the above-mentioned coating solution in a spray tank, spray it on the surface of the core in the form of a spray, spray the coating solution while stirring in the high-speed mixer, and heat it at 120°C at the same time to accelerate the evaporation of water to obtain a ternary positive electrode material substrate.

[0066] Step 4: The ternary positive electrode material substrate is subjected to secondary sintering in an oxygen atmosphere at a temperature of 650° C. for 10 hours to form a cobalt phosphate coating layer on the surface of the inner core to obtain a ternary positive electrode material.

[0067] Example 2 Step 1: Ni-Co-Mn precursor Ni 0.92 Co 0.04 Mn 0.04 (OH)2 and micro powder lithium hydroxide are mixed, wherein the molar ratio of Li to the transition metal in the nickel cobalt manganese precursor is 1.03:1, and a sintering is carried out in an atmosphere with an oxygen concentration of more than 93%. The first sintering includes first keeping the temperature at 500°C for 5 hours, then heating to 750°C and keeping the temperature for 15 hours, and then dispersing after cooling to obtain the core of the ternary positive electrode material.

[0068] Step 2: Weigh 327g of cobalt nitrate hexahydrate and completely dissolve it in water, wherein the mass ratio of cobalt nitrate to water is 1:5, to obtain a cobalt nitrate solution; dilute 8.6g of phosphoric acid in 10g of water to obtain a phosphoric acid solution; drop all of the phosphoric acid solution into the cobalt nitrate solution to obtain a mixed solution. Weigh 8g of lithium hydroxide and dissolve it in 40g of water to obtain a lithium salt solution; slowly drop the lithium salt solution into the mixed solution, and perform a liquid phase synthesis reaction to obtain a coating solution containing amorphous cobalt phosphate.

[0069] Step 3, weigh 10 kg of the above-mentioned core, disperse it in a high-speed mixer for 5 minutes, place the above-mentioned coating solution in a spray tank, spray it on the surface of the core in the form of a spray, spray the coating solution while stirring in the high-speed mixer, and heat it at 120°C at the same time to accelerate the evaporation of water to obtain a ternary positive electrode material substrate.

[0070] Step 4: The ternary cathode material substrate is subjected to secondary sintering in an oxygen atmosphere at a temperature of 600° C. for 8 hours to form a cobalt phosphate coating layer on the surface of the inner core to obtain a ternary cathode material.

[0071] Comparative Example 1 Step 1: Ni-Co-Mn precursor Ni 0.88 Co 0.08 Mn 0.04 (OH)2 and micro powder lithium hydroxide are mixed, wherein the molar ratio of Li to the transition metal in the nickel cobalt manganese precursor is 1.04:1, and a sintering is carried out in an atmosphere with an oxygen concentration of more than 93%. The first sintering includes first keeping the temperature at 500°C for 5 hours, then heating to 800°C for 15 hours, and then dispersing after cooling to obtain a ternary positive electrode material.

[0072] Comparative Example 2 Step 1: Ni-Co-Mn precursor Ni 0.88 Co 0.08 Mn 0.04 (OH)2 and micro powder lithium hydroxide are mixed, wherein the molar ratio of Li to the transition metal in the nickel cobalt manganese precursor is 1.04:1, and a sintering is carried out in an atmosphere with an oxygen concentration of more than 93%. The first sintering includes first keeping the temperature at 500°C for 5 hours, then heating to 800°C for 15 hours, and then dispersing after cooling to obtain the core of the ternary positive electrode material.

[0073] Step 2: Weigh 10 kg of the above-mentioned core and 142 g of cobalt phosphate powder, add them into a high-speed mixer and mix and coat for 15 minutes to obtain a ternary positive electrode material substrate.

[0074] Step 4: The ternary positive electrode material substrate is subjected to secondary sintering in an oxygen atmosphere at a temperature of 650° C. for 10 hours to form a cobalt phosphate coating layer on the surface of the inner core to obtain a ternary positive electrode material.

[0075] Comparative Example 3 Step 1: Ni-Co-Mn precursor Ni 0.92 Co 0.04 Mn 0.04(OH)2 and micro powder lithium hydroxide are mixed, wherein the molar ratio of Li to the transition metal in the nickel cobalt manganese precursor is 1.03:1, and a sintering is carried out in an atmosphere with an oxygen concentration of more than 93%. The first sintering includes first keeping the temperature at 500°C for 5 hours, then heating to 750°C and keeping the temperature for 15 hours, and then dispersing after cooling to obtain a ternary positive electrode material.

[0076] 1. The following tests were performed on the ternary positive electrode materials obtained in Examples 1-2 and Comparative Examples 1-3.

[0077] (I) The cobalt phosphate synthesized in the liquid phase obtained in Example 1 was observed by scanning electron microscopy. The results are as follows: Figure 3 The cobalt phosphate synthesized in the liquid phase obtained in Example 1 was subjected to an X-ray diffraction test, and the results were as shown in Figure 4 shown.

[0078] (ii) The electrical performance test conditions are as follows: the prepared ternary positive electrode material, conductive carbon and binder polyvinylidene fluoride are mixed evenly in a mass ratio of 92:5:3 to form a button battery. The LAND battery test system is used for constant current charge and discharge test. During the test, the working voltage range of the first discharge capacity test is 2.8V~4.3V, the charge and discharge rate is +0.1C / -0.1C, and the CV cut-off current is 0.01C; the working voltage range of the 45°C cycle test is 2.8V~4.3V, the charge and discharge rate is +1C / 1C, and the CV cut-off current is 0.01C. The first coulomb efficiency, first discharge capacity, and capacity retention rate after 100 cycles at 45°C of the battery prepared with the ternary positive electrode materials obtained in Examples 1-2 and Comparative Examples 1-3 were measured at a rate of 0.1C. The results are shown in Table 1.

[0079] The above results show that: Figure 3 This is a SEM image of the cobalt phosphate synthesized in the liquid phase in Example 1. It can be seen that the synthesized cobalt phosphate is nanoscale in size, which is conducive to the subsequent formation of a coating layer with good uniformity and continuity. Figure 4 This is the XRD diagram of the cobalt phosphate synthesized in the liquid phase in Example 1. The results show that the cobalt phosphate coating layer synthesized in Example 1 is amorphous. The amorphous material can provide lower interface impedance for the ternary positive electrode material and improve the electron and ion conduction efficiency of the ternary positive electrode material.

[0080] From the comparison between Example 1 and Comparative Example 1, and Example 2 and Comparative Example 3 in Table 1, it can be seen that the preparation method of the ternary positive electrode material provided in Examples 1-2 of the present application synthesizes amorphous cobalt phosphate from soluble cobalt salt, phosphoric acid and lithium salt solutions, and prepares a thin and uniform coating layer by spray coating. After the cobalt phosphate coating, the electrical performance first discharge and first efficiency of the ternary positive electrode material are significantly improved, and under high temperature conditions, the cycle stability of the ternary positive electrode material is significantly improved.

[0081] Example 1 adopts spray coating to prepare ternary positive electrode material, and Comparative Example 2 adopts dry coating of cobalt phosphate powder to prepare ternary positive electrode material. It can be seen from Example 1 and Comparative Example 2 that the positive electrode material of Example 1 has higher capacity and better high-temperature cycle stability than the positive electrode material of Comparative Example 1. This is mainly due to the liquid phase spray coating method, which has better coating uniformity, rather than the rough island coating of dry coating.

[0082] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a ternary positive electrode material, characterized in that: include: Mixing a nickel-cobalt-manganese precursor and a lithium source and sintering them once to obtain the core of the ternary positive electrode material; A phosphoric acid solution, a soluble cobalt salt solution and an alkali solution are mixed, and a coating solution containing amorphous nano-cobalt phosphate is synthesized through a liquid phase; The coating solution is used to spray and coat the inner core to obtain a ternary positive electrode material substrate; as well as The ternary positive electrode material substrate is subjected to secondary sintering to form a cobalt phosphate coating layer on the surface of the inner core, thereby obtaining the ternary positive electrode material.

2. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: The soluble cobalt salt in the soluble cobalt salt solution includes at least one of cobalt nitrate and cobalt acetate.

3. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: In the phosphoric acid solution, the mass ratio of phosphoric acid to water is 1:(1-2); In the soluble cobalt salt solution, the mass ratio of the soluble cobalt salt to water is 1:(1-5); The molar ratio of phosphoric acid in the phosphoric acid solution to cobalt in the soluble cobalt salt is (0.6-1):

1.

4. The method for preparing a ternary cathode material according to claim 1, characterized in that: The alkali solution is a lithium salt solution, and the lithium salt includes at least one of lithium hydroxide and lithium carbonate.

5. The method for preparing the ternary cathode material according to claim 4, characterized in that: In the lithium salt solution, the mass ratio of the lithium salt to water is 1:(1-5); The molar ratio of lithium in the lithium salt solution to cobalt in the soluble cobalt salt solution is (1.5-2):

1.

6. The method for preparing a ternary cathode material according to claim 1, characterized in that: The step of spraying the coating solution to coat the core further includes: The coating solution and the core are heated at a temperature of 100° C. to 120° C.

7. The method for preparing a ternary cathode material according to claim 1, characterized in that: The temperature of the secondary sintering is 500° C. to 700° C., and the time of the secondary sintering is 10 h to 12 h.

8. The method for preparing a ternary cathode material according to claim 1, characterized in that: The chemical formula of the nickel-cobalt-manganese precursor can be Ni x Co y Mn 1-x-y (OH)2, where 0.8≤x<1, 0 <y<0.2。 9. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared by the preparation method of the ternary positive electrode material according to any one of claims 1 to 8, wherein the ternary positive electrode material comprises an inner core containing a ternary positive electrode active material and a cobalt phosphate coating layer located on the surface of the inner core.

10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is the ternary positive electrode material as described in claim 9.

Citation Information

Patent Citations

  • Phosphorus-containing substance coated positive electrode material and preparation method and application thereof

    CN115117316A

  • Lithium aluminum indium phosphate-coated high-nickel lithium nickel cobalt tungstate positive electrode material and preparation method thereof

    CN115275088A

  • Modified ternary positive electrode material and preparation method thereof

    CN118198343A

  • Phosphorus-containing substance coated positive electrode material, preparation method therefor and use thereof

    WO2024007459A1